2022
DOI: 10.1101/2022.11.23.517619
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feline Coronavirus Infection of Domestic Cats Causes Development of Cross-Reactive Antibodies to SARS-CoV-2 Receptor Binding Domain

Abstract: The current study was initiated when our specific pathogen-free laboratory toms developed unexpectedly high levels of cross-reactive antibodies to human SARS-CoV-2 (SCoV2) receptor binding domain (RBD) upon mating with feline coronavirus (FCoV)-positive queens. Multi-sequence alignment analyses of SCoV2 Wuhan RBD and four strains each from FCoV serotypes 1 and 2 (FCoV1, FCoV2) demonstrated amino acid sequence identity of 11.5% and similarity of 31.8% with FCoV1 RBD, as well as 12.2% identity and 36.5% similari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Based on the temporal spread of the SARS-CoV-2-ELISA-positive sera, exposure of stray cats to Omicron BA.1 and consequently low cross-reactivity with the ancestral SARS-CoV-2 strain as used in the pseudo-VNT can insufficiently explain the lack of neutralizing antibodies. Cross-reactivity between antibodies induced by other coronaviruses that might infect stray cats was considered another explanation for the SARS-CoV-2-ELISA-positive results in the absence of SARS-CoV-2-neutralizing antibodies [ 50 , 84 , 85 ]. In this study, there was no association between the ELISA OD values of SARS-CoV-2 S1/RBD and FCoV S1 ( Figure S3A,B ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the temporal spread of the SARS-CoV-2-ELISA-positive sera, exposure of stray cats to Omicron BA.1 and consequently low cross-reactivity with the ancestral SARS-CoV-2 strain as used in the pseudo-VNT can insufficiently explain the lack of neutralizing antibodies. Cross-reactivity between antibodies induced by other coronaviruses that might infect stray cats was considered another explanation for the SARS-CoV-2-ELISA-positive results in the absence of SARS-CoV-2-neutralizing antibodies [ 50 , 84 , 85 ]. In this study, there was no association between the ELISA OD values of SARS-CoV-2 S1/RBD and FCoV S1 ( Figure S3A,B ).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, cross-reactivity between FCoV-specific antibodies and SARS-CoV-2 antigen had also been excluded in cats sampled since the SARS-CoV-2 pandemic [ 23 , 49 , 50 , 74 , 86 ]. In contrast to these studies, experimental FCoV-infected SPF cats showed cross-reactivity in a SARS-CoV-2 RBD-specific ELISA [ 85 ]. In addition, pre-pandemic sera from cats sampled in the USA tested positive in a SARS-CoV-2 RBD-specific ELISA [ 84 ].…”
Section: Discussionmentioning
confidence: 99%